Authigenic neodymium isotope data of sediment cores from the deep South Atlantic - Hallmaier, Moritz; Rückert, Eva M; Link, Jasmin M; Lütkes, Laura; Frank, Norbert (PANGAEA, 2025)
Here, we present neodymium isotope data (εNd) from three sediment cores from the Atlantic sector of the Southern Ocean (SO) to assess the distribution of water masses during the past 150 ka. The cores are located south of the modern polar frontal zone, building a vertical transect within the modern mixing zone of Circumpolar Deep Water and Antarctic Bottom Water. The data reveals a tremendous εNd variability, which reflects mainly water mass changes during climate transitions. It resolves systematic glacial-interglacial variations in the deep-water composition with strong evidence of a persistent admixture of Pacific sourced water into the SO during the past 150 ka which is the strongest during times of peak glacial ice extent. Mass spectrometric Nd isotope measurements were performed at the Institute of Environmental Physics multicollector ICPMS facility in Heidelberg, which hosts a ThermoFisher Neptuneplus MC-ICPMS coupled with an APEX HF desolvating system and an ESI-SC autosampler.
Keywords: Atlantic Ocean; glacial-interglacial cycles; Holocene; LGM; Neodymium isotopes; neodymium (Nd); ODP; ODP 1093; ODP 1094; sediment; Southern Ocean; water mass tracing